Public Information and Coordination: Evidence from a Credit Registry Expansion - HERTZBERG, ANDREW; LIBERTI, JOSÉ MARÍA; PARAVISINI, DANIEL (Journal of Finance, 2011)
ABSTRACT This paper provides evidence that lenders to a firm close to distress have incentives to coordinate: lower financing by one lender reduces firm creditworthiness and causes other lenders to reduce financing. To isolate the coordination channel from lenders' joint reaction to new information, we exploit a natural experiment that forced lenders to share negative private assessments about their borrowers. We show that lenders, while learning nothing new about the firm, reduce credit in anticipation of other lenders' reaction to the negative news about the firm. The results show that public information exacerbates lender coordination and increases the incidence of firm financial distress.